Questionnaire-based eye screening tool for people with disabilities (QBEST-PWD) / AH Chen, NFA Bakar and CYW Hoe - Chen, A.H; Bakar, N.F.A; Hoe, C.Y.W (2020)
Questionnaire-Based Eye Screening Tool for People with Disabilities (QBEST-PWD) is developed to tackle the lack of disabled friendly eye care services in our society today. In a world that is not designed for the disabled, they often experience difficulty with accessibility to health services. Existing instrumentbased vision screening is less than ideal for people with disabilities due to mobility constraint. Inaccessibility to eye-care services may have negative impact on their quality of life. There were three phases of the QBEST-PWD innovation process: (1) idea generation to enhance eye care accessibility for people with disabilities; (2) problem solving tactic to remove the dependency on instruments in existing vision screening style; (3) implementation – by substituting inconvenient instrument-based vision screening with a new questionnaire-based vision screening. Criteria setting and content were rigorously analyzed to preserve sensitivity and specificity. Conceptual model development also incorporated wide-ranging vision elements. A two-tier eye screening modus that embedded screening items with respective probing items was established. QBEST-PWD can be used as a complementary or a standalone screening apparatus for disabled people whom have accessibility difficulties to eyecare facilities.